Large raptors in “Nurgush” State Nature Reserve, Kirov region, Russia - Sergei V. Bakka; Nadezhda Yu. Kiseleva; Svetlana V. Kondruhova (Пернатые хищники и их охрана)
In this report, we explored the nature of stay and the number of large raptors in “Nurgush” State Nature Reserve in Kirov region, assessed the role of the reserve in conservation of these birds.